Characterization of P. vivax blood stage transcriptomes from field isolates reveals similarities among infections and complex gene isoforms - Kim, Adam; Popovici, Jean; Vantaux, Amélie; Samreth, Reingsey; Bin, Sophalai; Kim, Saorin; Roesch, Camille; Liang, Li; Davies, Huw; Felgner, Philip; Herrera, Sócrates; Arévalo-Herrera, Myriam; et al. (Scientific reports, 2017)
Our understanding of the structure and regulation of Plasmodium vivax genes is limited by our inability to grow the parasites in long-term in vitro cultures. Most P. vivax studies must therefore rely on patient samples, which typically display a low proportion of parasites and asynchronous parasites. Here, we present stranded RNA-seq data generated directly from a small volume of blood from three Cambodian vivax malaria patients collected before treatment. Our analyses show surprising similarities of the parasite gene expression patterns across infections, despite extensive variations in parasite stage proportion. These similarities contrast with the unique gene expression patterns observed in sporozoites isolated from salivary glands of infected Colombian mosquitoes. Our analyses also indicate that more than 10% of P. vivax genes encode multiple, often undescribed, protein-coding sequences, potentially increasing the diversity of proteins synthesized by blood stage parasites. These data also greatly improve the annotations of P. vivax gene untranslated regions, providing an important resource for future studies of specific genes.